2023
DOI: 10.1007/jhep04(2023)005
|View full text |Cite
|
Sign up to set email alerts
|

Aligned fields double copy to Kerr-NUT-(A)dS

Abstract: We find Abelian gauge fields that double copy to a large class of black hole spacetimes with spherical horizon topology known as the Kerr-NUT-(A)dS family. Using a multi-Kerr-Schild prescription, we extend the previously-known double copy structure for arbitrarily rotating general dimension black holes, to include NUT charges and an arbitrary cosmological constant. In all cases, these single copy gauge fields are ‘aligned fields’, because their nonzero components align with the principal tensor which generates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 80 publications
(119 reference statements)
0
0
0
Order By: Relevance
“…Therefore, while it is not shocking, neither is it obvious to us why the double copy should respect the hidden symmetry of Kerr. Our results do seem related to those of [30] though, where it was found that the single copy gauge field corresponding to a Kerr-NUT-(A)dS spacetime [42] has a field strength that is "aligned" [46] with (but not proportional to) the spacetime's principal tensor [47]. The principal tensor controls the Killing tensors of Kerr-NUT-(A)dS, as reviewed in [48], so their results provide further evidence that the double copy somehow respects hidden symmetries.…”
Section: Jhep10(2023)085 6 Discussionsupporting
confidence: 84%
“…Therefore, while it is not shocking, neither is it obvious to us why the double copy should respect the hidden symmetry of Kerr. Our results do seem related to those of [30] though, where it was found that the single copy gauge field corresponding to a Kerr-NUT-(A)dS spacetime [42] has a field strength that is "aligned" [46] with (but not proportional to) the spacetime's principal tensor [47]. The principal tensor controls the Killing tensors of Kerr-NUT-(A)dS, as reviewed in [48], so their results provide further evidence that the double copy somehow respects hidden symmetries.…”
Section: Jhep10(2023)085 6 Discussionsupporting
confidence: 84%
“…Similarly, the Taub-NUT spacetime in four dimensions can be written in double Kerr-Schild form, and in D dimensions it can analogously be written in a multi-Kerr-Schild form with D/2 mutually orthogonal null geodesics [43]. This multi-Kerr-Schild coordinate system enables a double copy interpretation of these metrics in four and higher dimensions [11,44]. The connection between these results and the generalization of the sKS ansatz to include NUT charge is worthy of further study.…”
Section: Jhep05(2023)198mentioning
confidence: 99%